Aspectos ultra-estruturais da fibra muscular cardíaca de ratas albinas durante o ciclo gravídico-puerperal - Liberatori Filho, Aroldo Walter [UNIFESP] (1999)
PURPOSE. In the present study we evaluated the morphology of left ventricular cardiomyocytes of albino rats during pregnancy and puerperium by means of transmission electron microscopy. METHODS. Once pregnancy was confirmed, 77 rats were randomly divided in two groups, respectively, gestation (G) and puerperium ( P). The animals of the gestation group were divided into four subgroups, according to gestational age: 1st (G-A), 7th (G-B), 14th (G-C) and 21st (G-D) days of pregnancy. The group defined as puerperium was divided into three subgroups: 7th (P-A), 14th (P-B) and 21st (P-C) days of puerperium. In the end of each established period, the animals were sacrificed and fragments of the medium third of the left ventricle were resected and routinely prepared for electron microscopy analysis. RESULTS. The results obtained with transmission electron microscopy analysis revealed a gradative increase of the cardiomyocytes during pregnancy (increase of myofibrils, which are permeated by numerous mitochondria at the end of gestation). The blood capillary wall showed progressive thinning, with an increase of pynocytotic vesicles in endothelial cells, and intense sarcolemal folding at T- tubule level (capillary tunnels). In the puerperium group, there is a progressive regression in these alterations returning to pre-gestational level at the end of the puerperium cycle. These findings indicate the occurrence of hypertrophy of cardiomyocytes during pregnancy. CONCLUSION. The findings indicate the occurrence of hypertrophy of cardiomyocytes during pregnancy.